1997
DOI: 10.1002/(sici)1099-0518(199702)35:3<407::aid-pola3>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photoinitiated cationic polymerization of monomers with the silsesquioxane core

Abstract: A synthetic scheme was developed to prepare cationically polymerizable octafunctional monomers with silsesquioxane (TJ cores. Epoxy and 1-propenoxy functional groups were attached to the core by the hydrosilation of T~with an appropriate precursor. The steric constraintsand the requirementsfor the hydrosilationreaction are discussed.The monomers were fully characterized and then polymerized by exposure to ultraviolet irradiation in the presence of onium salt photoinitiators. The polymerization conditions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…POSS with one or more covalently bonded reactive groups is suitable for polymerization, grafting, surface bonding, blending and other transformations to build organic/inorganic hybrid materials at the molecular level. [9][10][11][12][13] POSS functionalized with groups such as hydrogen, 14 amine, 15 vinyl, 16 epoxy 17 and isocyanate 18 can be used as monomers or comonomers in typical polymerizations. One such POSS, hydrogen silsesquioxane (HSQ), has attracted increasing interest in scientific research and technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…POSS with one or more covalently bonded reactive groups is suitable for polymerization, grafting, surface bonding, blending and other transformations to build organic/inorganic hybrid materials at the molecular level. [9][10][11][12][13] POSS functionalized with groups such as hydrogen, 14 amine, 15 vinyl, 16 epoxy 17 and isocyanate 18 can be used as monomers or comonomers in typical polymerizations. One such POSS, hydrogen silsesquioxane (HSQ), has attracted increasing interest in scientific research and technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Silsesquioxanes are a class of compounds well known for their high temperature stability [4]. Recently a series of Polyhedral Oligomeric Silsesquioxanes (POSS) has been developed [15], all of which involve a robust silicon-oxygen cage framework with dimension of about 1-3 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have synthesized a wide variety of POSS nanoparticle structures and investigated their incorporation into several thermoset and thermoplastic polymer matrices [1][2][3][4][5][6][7][8][9][10][11]. The surface of the POSS structure is often modified with reactive or otherwise "functional" groups to foster improved compatibility and/or covalent bonding with the host matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It has nanometer-size cubic structure with wide surface area and controlled porosity, and can be functionalized with a wide variety of organic groups as monomer in a typical polymerization. Use of POSS derivatives as monomer has been demonstrated to be an efficient method in the design of nanocomposite materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] as well as in designing various hybrid polymers with POSS as side groups [16][17][18][19][20][21][22][23][24][25][26][27][28] or as chain end, [29][30][31] which exhibit desirable unique properties. Laine et al reported the synthesis of multi-functinal POSS as precursors of nanocomposite materials from commercially available typical silane-functionalized cubic silsesquioxane, octakis(dimethylsiloxy)octasilsesquioxane (Q 8 M 8 H ) by hydrosilylation.…”
mentioning
confidence: 99%